Coaching and Development of Pencak Silat Sports Based on Living Respect Values in Positive Youth Development - Jeki Purnama Putra; Nurlan Kusmaidi; Mulyana; Amung Ma’mun (UNIB Press, 2023)
This study aims to examine whether the integration of the concept of